Hubungan Antara Kecerdasan Emosional Dengan Prokrastinasi Akademik Dalam Menyelesaikan Tugas Akhir Pada Mahasiswa Psikologi Unversitas Medan Area - Rangga Muzakir Azwan; Salamiah Sari Dewi (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
This study aims to determine the relationship between emotional intelligence and academic procrastination in completing final assignments among Psychology students at Medan Area University. Academic procrastination is a procrastination behavior often carried out by students when facing important tasks, including their thesis, which can impact graduation delays and decrease learning motivation. Psychological factors, such as emotional intelligence, are thought to influence this procrastination tendency. Emotional intelligence encompasses an individual's ability to recognize, understand, manage, and express emotions healthily, as well as establish positive interpersonal relationships. Students with high emotional intelligence tend to be better able to cope with pressure, manage academic stress, and maintain focus on their academic goals. This study used a quantitative approach with a correlational method to examine the relationship between the two variables. The subjects in this study were 80 final-year students who were in the process of preparing their final assignments. The sampling technique used was purposive sampling, with the criteria being active students who were writing their thesis. The instruments used consisted of an emotional intelligence scale and an academic procrastination scale compiled based on relevant theoretical indicators. Data analysis was performed using the Pearson correlation test. The analysis results show a significant negative relationship between emotional intelligence and academic procrastination. This means that the higher a student's emotional intelligence, the lower their level of academic procrastination. This finding suggests that emotional intelligence plays a crucial role in supporting students in completing their final assignments on time. Therefore, developing emotional intelligence through psychological training or guidance could be a strategy to reduce procrastination among students.